2008
DOI: 10.1513/pats.200708-137mg
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Obstructive Sleep Apnea: Pathogenic Mechanisms and Therapeutic Approaches

Abstract: Obstructive sleep apnea is a common disorder whose prevalence is linked to an epidemic of obesity in Western society. Sleep apnea is due to recurrent episodes of upper airway obstruction during sleep that are caused by elevations in upper airway collapsibility during sleep. Collapsibility can be increased by underlying anatomic alterations and/or disturbances in upper airway neuromuscular control, both of which play key roles in the pathogenesis of obstructive sleep apnea. Obesity and particularly central adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
416
4
23

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 584 publications
(455 citation statements)
references
References 192 publications
(203 reference statements)
12
416
4
23
Order By: Relevance
“…Obesity is strongly associated with an increased prevalence of sleep apnea 25, 26. Sleep apnea severely impairs health‐related quality of life 26.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is strongly associated with an increased prevalence of sleep apnea 25, 26. Sleep apnea severely impairs health‐related quality of life 26.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled study, John et al reported that bariatric surgery did not result in a significantly greater reduction in AHI than conventional weight loss therapy, although the former did result in more weight loss [25]. They suggested that the state rather than the extent of weight loss was important in generating an altered neurohumoral and metabolic-inflammatory milieu, influencing defects in neuromuscular responses to mechanical loads [26,27]. Furthermore, the modified gastrointestinal anatomy and physiology may influence the effect of bariatric surgery on OSA, although no evidence has been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…22 Obesity has also been implicated in anatomical changes that predispose patients to upper airway obstruction and reduced neuromuscular control of the air passages during sleep. 23,24 Obesity accelerates the initial onset and progression of physical disability in older adults. 25 Maternal obesity is associated with an increased risk for congenital anomalies.…”
Section: Us Endocrinologymentioning
confidence: 99%